1967
DOI: 10.3758/bf03327861
|View full text |Cite
|
Sign up to set email alerts
|

Unrewarded trials and resistance to extinction of a bar-pressing response

Abstract: Two experiments in a free-operant situation tested the generality of Lawrence & Festinger's (1962) hypothesis that the total number of nonreinforced trials, not percentage of reward, is the critical variable in determining resistance to extinction. This was supported by Experiment 1. However, when rate of responding was held constant in Experiment 2 the hypothesis was not supported. The results suggest that S's with faster rates of responding in acquisition make more responses in extinction indicating an energ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

1968
1968
1974
1974

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 2 publications
0
2
0
Order By: Relevance
“…In the continuous trial situation, resistance to extinction is a function of the absolute number of nonreinforced trials (Dutch and Quartermain, 1967). This suggests that "persistence," defined as a specific energy or work requirement, is necessary for PR to be effective in obtaining a PRE.…”
mentioning
confidence: 99%
“…In the continuous trial situation, resistance to extinction is a function of the absolute number of nonreinforced trials (Dutch and Quartermain, 1967). This suggests that "persistence," defined as a specific energy or work requirement, is necessary for PR to be effective in obtaining a PRE.…”
mentioning
confidence: 99%
“…They suggest that in the free operant situation response chaining may occur and that this may result in a confounding of response patterns from the feedback stimulation from any trial or trials. Dutch & Quartermain (1967) in a between-S free operant experiment observed a faster response rate in acquisition and greater resistance to extinction for groups receiving hig~er numbers of nonreinforced trials. They suggested that nonremforcement increased the speed of responding in acquisition, and that the faster the rate in acquisition, the higher the extinction score.…”
mentioning
confidence: 99%